The (doubtful) role of financial reward in obedience to authority - Dolinski, Dariusz; Grzyb, Tomasz (The Journal of social psychology, 2019)
The Milgram experiments are among the most well-known and important in the history of psychology. Since first published, there have been countless discussions held on the subject of what factors induce people to exhibit extreme obedience towards authority. One such potential factor, not yet explored empirically, is the receipt in advance of financial gratification by a study participant. In our experiment we compare obedience among participants in classic Milgram paradigm conditions with obedience in a situation where the participant does not receive financial gratification in advance. The results did not show that obedience differed in the two comparable situations. In conditions where the participants were not given money up front, however, it was necessary to employ more verbal prompts in order to induce obedience.